STUDY ADSORPTION DESORPTION OF MANGANESE(II) USING IMPREGNATED CHITIN-CELLULOSE AS ADSORBENT - Aldes Lesbani; Ema Veronika Turnip; Risfidian Mohadi; Nurlisa Hidayati (International Journal of Science and Engineering, 2015)
Abstract- Study adsorption desorption of manganese(II) using impregnated chitin-cellulose as adsorbent has been carried out. Chitin was extracted from snail shell and cellulose isolated from rice straw. Chitin and cellulose were impregnated using thiourea as impregnant agent. Characterization of chitin and cellulose was performed using FTIR spectroscopy, determination of water content, and ash content, while impregnated chitin-cellulose was characterized using FTIR spectrophotometer and X-Ray diffractometer. The adsorption of Mn(II) on impregnated chitin-cellulose was studied through determination of adsorption time and the influence of Mn(II) concentration, while desorption was carried out sequentially using various reagents. The results shown that chitin and cellulose from extraction processes are has similar FTIR spectrum compared to chitin and cellulose standard. The FTIR spectrum of impregnated chitin-cellulose shows both vibration of chitin and cellulose appeared and indicated successfully impregnate. These results were also equal to XRD pattern analysis. The water and ash contents of chitin are 0.038% and 0.043 while for cellulose are 0.184% and 0.165%, respectively. The adsorption of Mn(II) on chitin and cellulose are quite similar kinetically, while adsorption of Mn(II) on impregnated chitin-cellulose is higher at the same time with chitin and cellulose. In the low concentration of Mn(II), adsorption phenomena are similar on chitin, cellulose, and impregnated chitin-cellulose. Desorption process of Mn(II) on the adsorbents shows sodium etilenediamine tetra acetate able to desorp Mn(II) up to 68% higher than other reagents. Keywords: Manganese(II), Chitin, Cellulose, Impregnated Chitin-Cellulose